The impact of the catalyst layer structure on phosphoric acid migration in HT-PEFC – An operando X-ray tomographic microscopy study - Halter, J.; Bevilacqua, N.; Zeis, Roswitha; Schmidt, T. J.; Büchi, F. N. (Journal of Electroanalytical Chemistry, 2020)
Acid migration and loss at high current densities has previously been identified as an important degradation mechanism for phosphoric acid in high temperature polymer electrolyte fuel cells. In this process, the structure of the anode catalyst layer plays an important role for the acid migration mechanism. Therefore, the acid retaining capabilities of two significantly different catalyst layer structures were investigated by means of operando X-ray tomographic microscopy. In a commercial catalyst layer, with cracks with a mean width of 39 μm, ideal crack connectivity and no bottlenecks in the crack structure, phosphoric acid penetrates and traverses the catalyst layer and migrates to the GDL and gas channel. In contrast, an in-house catalyst layer retained phosphoric acid within itself. Although with lower mean crack size of only 20 μm, the different crack connectivity and accessibility, as determined by crack width and simulated mercury intrusion crack size analysis, were identified as main causes for better acid retaining capabilities. A fraction of over 95% of the crack-volume is protected by bottlenecks smaller than 20 μm. The present analysis is a guideline for engineering acid retaining catalyst layers structures for high temperature polymer electrolyte fuel cells.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Catalyst layer cracks; High temperature polymer electrolyte fuel cell; Lifetime; Mitigating electrolyte losses; Phosphoric acid; X-ray tomographic microscopy